(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The European Charter for Equality of Women and Men in Local Life (2006) was first presented at the 6th Council of Europe’s European Ministerial Conference and at the meeting of the Committee on Women’s Rights and Gender Equality of the European Parliament in 2006 as an extension of the “Cities for Equality” initiative of the Council of European Municipalities and Regions (CEMR). Adoption and active application of the principles and rules of the above-mentioned European Charter are the foundation of the political and social life at a local level. Furthermore, they are of utmost importance for promoting equality of women and encouraging their stronger political engagement in order to achieve true gender equality. By the end of 2018, only 27 local and regional self-government units signed the European Charter in the Republic of Croatia, three of which were municipalities, twelve cities and twelve counties. The representation of women in representative bodies of local and regional government is extremely low in the Republic of Croatia, and the society’s lack of interest in any changes aimed at greater participation of women in the political life of the state is evident. This serious state of affairs first and foremost necessitates local and regional self-governments adopting the European Charter, which provides clear guidelines for the implementation of the principles of equality of women and men at the local level, and strengthens the participation of women in the political life of the local community and beyond. Although little has been written about the European Charter in scholarly and professional papers, it is a platform which can be upgraded with a number of positive actions for raising the awareness of the local public, with a view to a more effective implementation of the principle of gender